تصور مقترح لتنظيم الإرشاد الأكاديمي بالجامعة في ضوء التوجهات العالمية - الأسود, الزهرة (My University, 2018)
يعتبر الإرشاد الأكاديمي عملية توجيهية تتضمّن ثلاث مجالات رئيسة هي: الإعلام، التوجيه، الإرشاد؛ وهي بمثابة خدمات ضرورية لإعداد الطالب الجامعي إعدادا متكاملا نفسيا واجتماعيا وأكاديميا لمواجهة صعوبات الحياة والتكيّف معها بشكل عام، ومواكبة الحياة الجامعية والتكيّف معها بشكل خاص لا سيما أن خدمات الإرشاد الأكاديمي أصبحت هدفا بارزا من أهداف التعليم العالي الرامية إلى بناء شخصيات متفاعلة مع مجتمع متغيّر ومتسارع. والمرشد الأكاديمي يسعى لمساعدة الطالب على اكتشاف قدراته، ويسهّل له توظيفها في حلّ ما قد يعترضه من صعوبات، مما يحقّق له النجاح والتفوّق في الدراسة. ولكي ينفّذ المرشد الأكاديمي هذه المهمّة التربوية بنجاح، لا بدّ أن يستند على خطة عمل توضّح مهامه الإرشادية والأهداف التربوية التي ينبغي تحقيقها لصالح تكيّف الطالب أكاديميا، وهذا بدوره يسهم في إنجاح العملية التعليمية، وتحقيق الجامعة لرسالتها في خدمة المجتمع. وعليه، جاءت هذه الورقة لتعرض تصوّرا مقترحا لتنظيم الإرشاد الأكاديمي بالجامعة في ضوء التوجهات العالمية. Abstract: Academic guidance is a guiding process involving three main areas: Information, orientation and guidance; which are necessary services for preparing the university student psychologically, socially and academically to cope and adapt with the difficulties of life in general, and to keep pace and adaptation with university life in particular, especially that the services of academic guidance has become a prominent goal of higher education that aims to build interactive personalities with accelerated changing society. The academic advisor seeks to help the student to discover his abilities, and makes it easier for him to employ them in solving the difficulties he may face, and allow him to achieve success and excellence in the study. In order for the academic advisor to carry out this educational task successfully, it must be based on a plan of action that clarifies his instructional tasks and the educational goals that should be achieved in order to adapt the student academically. This in turn contributes to the success of the educational process, and to achieve the University's mission in the service of society. Accordingly, this paper presents a proposed vision for organizing the academic guidance of the university in the light of global trends.
مؤتمر التعليم في الوطن العربي - الجامعة الأردنية كلية العلوم التربوية
Keywords: الإرشاد الأكاديمي؛ المرشد الأكاديمي؛ الجامعة؛ التوجهات العالمية; Academic guidance; The academic advisor; The university; Global trends